Strong flexible polymer/graphene composite films with 3D saw-tooth folding for enhanced and tunable electromagnetic shielding. (March 2017) - Shen, Bin; Li, Yang; Yi, Da; Zhai, Wentao; Wei, Xingchang; Zheng, Wenge
Abstract: Strong flexible polymer/graphene composite films with ideal electromagnetic interference (EMI) shielding are fabricated through constructing a sandwich structure consisting of polyester non-woven fabric as reinforcing interlayer and thermoplastic polyurethane (TPU) composite with high graphene loading as conductive coating layer. The engineered sandwich film (defined as TPU/G film) with graphene loading of ∼20 wt% and total coating thickness of ∼50 μm not only possesses excellent mechanical flexibility and strong strength, but also exhibits qualified bandwidth of shielding effectiveness (SE) ≥ 20 dB as wide as ∼49.1 GHz in a broadband frequency range of 5.4–59.6 GHz. Moreover, saw-tooth folding of the flexible TPU/G films could efficiently enhance the shielding performance, and more conductive folded film with smaller included angle plus longer side would result in much greater SE enhancement along with reduced EM reflection. This finding also realizes the convenient performance regulation of the folded TPU/G films through a simple mechanical deformation, showing promise for tunable EMI shielding. Graphical abstract: Strong flexible polymer/graphene composite films with ideal electromagnetic interference (EMI) shielding are fabricated through constructing a sandwich structure consisting of polyester non-woven fabric as reinforcing interlayer and thermoplastic polyurethane (TPU) composite with high graphene loading as conductive coating layer. The engineered sandwich film (defined as TPU/G film) with graphene loading of ∼20 wt% and total coating thickness of ∼50 μm not only possesses excellent mechanical flexibility and strong strength, but also exhibits qualified bandwidth of shielding effectiveness (SE) ≥ 20 dB as wide as ∼49.1 GHz in a broadband frequency range of 5.4–59.6 GHz. Moreover, saw-tooth folding of the flexible TPU/G films could efficiently enhance the shielding performance, and more conductive folded film with smaller included angle plus longer side would result in much greater SE enhancement along with reduced EM reflection. This finding also realizes the convenient performance regulation of the folded TPU/G films through a simple mechanical deformation, showing promise for tunable EMI shielding.